EKSISTENSI JURNALIS PEREMPUAN DALAM MEMPERTAHANKAN KESETARAAN GENDER DI INSPIRA TV BANDUNG - Ridwan Mustopa; Achmad Wildan Kurniawan; Susi Septianti (Commed : Jurnal Komunikasi dan Media, 2022)
This research is motivated by the problem of gender equality that still often occurs. The main cause of the gender gap is social values, meanwhile the ability, willingness, and readiness of women themselves to change the situation are not actually implemented. The purpose of this study is to explain how female journalists maintain gender equality amidst the patriarchal social structure in terms of motives, experiences and meanings. This study uses a qualitative descriptive method and using the phenomenological theory of Alfred Schutz and Husserl. While the data collection techniques used in this study were through observation, interviews and documentation studies. The subjects in this study were female journalists at Inspira Tv Bandung, to determine the informants, the researchers used Snow Ball Sampling. The results of this study indicate the characteristics of the motives of female journalists at Inspira Tv Bandung assessing that the work of journalists is a noble job and is a pleasure in reporting. Based on the characteristics of the experience, several female journalists at Inspira Tv Bandung had negative experiences such as verbal harassment, being looked down upon and being seconded. on the characteristics of the meaning of female journalists on Inspira Tv Bandung interpreting it with feelings, not being underestimated because of gender and some journalists interpret it by working professionally and with quality.